Analysis and Optimization of Employability for Engineering Graduates in Ethiopia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Higher education and universities are required to play a critical role in any country's technological transition and growth. The university based descriptive cross sectional study will be conducted from the graduates passed out from two universities and an optimization study has been done how the employability rate has been decided in Ethiopia using Ant colony Optimization (ACO). The optimized employability rate was calculated using information gathered from graduated students' responses to Google forms sent to their respective email addresses. The study includes 1100 users from 1500 graduate from engineering and technology students of Bule Hora and Hawassa universities,Ethiopiagraduated from 2018 and 2019 GC.  The results shows around 75% of the graduates were employed and in that majority (90%) of them in their respective field of study. The 80% of the graduates suggested internship is useful to get their jobs and 90% wants to improve the practical skill of the students in the universities. The results gives the optimized employability rate is decided first by Grade earned and location near to their home town  secondpractical knowledge of the student, and third skill development in the university, and Internship experience